Evaluation of Small and Medium Business Support Efficiency - Štreimikienė, Dalia; Dapkus, Rimantas; Šivickas, Gintautas (Ekonomika, 2007)
Small and medium-sized enterprises (SME) play a major role in economic growth and provide major external benefits such as creation of new jobs and increase in employment. Increase of employment is the main social policy or the government. As in the case or public goods, the SMEs faces market failures and other barriers. Therefore, SMEs have specific strengths and weaknesses that require special policy responses. SMEs face many problems: lack of financing, difficulties in exploiting technology, constrained managerial capabilities, low productivity. regulatory burdens. The government should improve SMEs access to financing, information infrastructures and international markets. Providing the regulatory, legal and financial frameworks conductive to entrepreneurship and small firm start-up and growth is a priority.Government policy initiatives should take account of the regional and local factors that affect entrepreneurship and on this basis to foster the partnership of small firms. Building on local strengths. SME policies need to address the new dynamics of entrepreneurship, and small firm clusters should meet the challenges of globalization.Fostering public-private partnerships and small-firm networks and clusters may be the most expeditious path to a dynamic SME sector. Grouped in the local system of production, SME arc more flexible and responsive to customer needs than large integrated firms. They can pool resources, share costs of training, research and marketing. Clustering facilitates exchange of personnel and diffusion of technology, creates efficiency gains and helps to meet the challenges of globalization. SME in clusters seek international opportunities also through strategic alliances, franchising and joint ventures.Clusters are geographic concentrations of interconnected companies, specialized suppliers, service providers, firms in related industries, and associated institutions (e.g., universities, standards agencies, trade associations) in a particular field that compete but also cooperate. Clusters, or critical masses of unusual competitive success in particular business areas, are a striking feature of virtually every national, regional, state, and even metropolitan economy, especially in more advanced nations. Clusters represent a new way of thinking about national, state, and local economics, and they necessitate new roles for companies, for various levels of government, and for other institutions in enhancing competitiveness. For companies, the thinking about competition and strategy has been dominated by what goes on inside the organization. Clusters suggest that a good deal of competitive advantage lies outside companies and even outside their industries. residing instead in the locations at which their business units arc based. This creates important new agendas for management that are rarely recognized. For example, clusters represent a new unit of competitive analysis along with the firm and industry. Cluster thinking suggests that companies have a tangible and important stake in the business environments where they are located, in ways that go far beyond taxes, electricity costs, and wage rates. The health of the cluster is important to the health of the company. Companies might actually benefit from having more local competitors. Trade associations can be competitive assets, not merely lobbying and social organizations. Clusters are important because they allow companies to be more productive and innovative than they could be in isolation. And clusters are important because they reduce the barriers for new business creation relative to other locations.The article deals with criteria for the government support to SME efficiency. A methodology of government support efficiency evaluation based on sustainability criteria is proposed. The criteria for selection of SME support measures should address all dimensions of sustainable development: social, economic and environmental. The methodology can be applied on country, region or enterprise level. Economic indicators for support effectiveness evaluation on enterprise level include the positive changes in financial indicators of a company on receiving support. Social indicators on such level arc the new jobs created and the increase of income. Environmental indicators such as pollutant emission reductions in an enterprise allow to evaluate the social effect of support. Therefore, a complex system of indicators needs to be developed to evaluate the efficiency of support provided to SMS according to economic, social and environmental criteria. The system of sustainability criteria may be applied on a country level and include more general indicators such as: GDP growth, increase of employment, higher real income of population, decrease of inequality of income, pollution reduction in the country, etc.